UPAYA PENINGKATAN KUANTITAS DAUN MURBEI (Morus alba) DENGAN MACAM PUPUK NITROGEN DAN TINGGI PEMANGKASAN - Juwarman Juwarman; Murti Astiningrum; Agus Suprapto (JURNAL VIGOR, 2016)
Research on efforts to increase the quantity of leaves of mulberry (Morus alba) with a wide high-nitrogen fertilizer and pruning was conducted in August and October 2015. The research location PPUS Candiroto KBM Agroforestry Perum Perhutani Unit I Central Java, in the district of Temanggung. Altitude of 600 m above the surface laut.Jenis latosol soil with a pH of 6. The research was conducted using a split plot experiment (3x3) are arranged in a complete randomized block design, repeated three times. The first factor is kind of Phonska nitrogen fertilizer, Urea and ZA. The second factor is high trimming 40, 60 and 80 cm from the ground. The results showed that fertilization using nitrogen fertilizers can promote the growth of ZA shoot length, shoot number, leaf number, stem diameter shoots, shoots fresh weight and dry weight of shoots on mulberry plants. High-trimming 60 cm of the soil surface increases the best results in the long shoots, shoot number, leaf number, stem diameter shoots, fresh weight tu-nas, and dry weight of shoots on mulberry plants.